Dosimetric Comparison of Different 3DCRT Techniques in Left Breast Cancer Radiotherapy Planning (Bangladesh Journal of Nuclear Medicine, 2016)
Treatment plan of 10 patients with left-sided breast cancer treated to a prescribed dose of 50 Gy in 25 fractions were selected. The treatment plans were generated by using an Elekta Precise PLAN treatment plan system (TPS) in three different ways namely M1 method, M2 method and M3 method for evaluation of dosimetric parameters based on three dimensional conformal radiotherapy (3DCRT) technique. Pencil beam calculation algorithm was used for dose calculation of Planning Treatment Volume (PTV) as well as Organ At Risk (OAR), with heterogeneity corrections. Plans were compared according to dose-volume histogram (DVH) analysis in terms of PTV homogeneity and conformity indices (HI and CI) as well as OARs dose and volume parameters. All the three treatment methods achieved comparable radiation dose delivery to PTV-95% of the prescribed dose covering > 95% of the breast PTV. The mean volume of PTV receiving 105% (V105) of the prescribed dose was 2.12% (range 0 - 5.7%) for M1 plan, 1.9% for M2 plan, and 3.08% for M3 plan. The homogeneity and conformity indices (HI and CI) were similar for M1 plan and M2 plan, whereas the M3 plan had better conformity index at the cost of less homogeneity. The low-dose volumes (V5Gy) in the heart and lungs were larger in M1 plan than in the other methods. The value of the mean dose to the ipsilateral lung was higher for M2 plan than the values for with M1 plan and M3 plan. Compared with M1 and M3 plan, M2 plan proved to be a simple planning method for 3DCRT breast irradiation.Bangladesh J. Nuclear Med. 17(2): 108-113, July 2014